Pyridoxine requirement of Pacific white shrimp (Penaeus vannamei) fed soybean meal based diet - Han-Se Kim; Yeonji Lee; Mirasha Hasanthi; Kyeong-Jun Lee (PLoS ONE, 2026)
This study aimed to determine the dietary pyridoxine requirement of Pacific white shrimp ( Penaeus vannamei ) fed a soybean meal–based diet. Seven experimental diets were prepared with graded pyridoxine supplementation at 0, 25, 50, 75, 100, 125, and 150 mg/kg diet (Con, P25, P50, P75, P100, P125, and P150, respectively). An additional negative control diet (Con − ) was formulated by adding 0.4% tetracycline hydrochloride to verify microbial synthesis of pyridoxine. Juvenile shrimp (initial weight: 0.38 g) were randomly assigned to eight diets with quadruplicate tanks and fed the diets for 45 days. Growth performance and feed utilization were increased with dietary pyridoxine supplementation up to P75, whereas higher supplementation levels resulted in reduced responses ( P < 0.001). Hepatopancreas pyridoxine concentration was gradually increased with increment in dietary pyridoxine levels ( P < 0.001), reaching a plateau from P75 to P150, and remained lower in Con − group than in Con group. Non-specific immune response, including lysozyme, anti-protease and nitroblue tetrazolium activities and antioxidant capacities including superoxide dismutase and glutathione peroxidase were significantly increased by dietary pyridoxine supplementation ( P < 0.05). Digestive enzyme activities, intestinal morphological indices, and hepatopancreatic F- and B-cell prevalence were also positively influenced by dietary pyridoxine supplementation ( P < 0.05). Gene expression analysis showed increased transcription of cystathionine-γ-lyase, cystathionine-β-synthase, pyridoxal kinase, crustin, and penaeidine in response to pyridoxine supplementation. Based on a broken-line regression analysis of weight gain, the dietary pyridoxine requirement was estimated to be 69.0 mg/kg diet.